O trabalho educativo com alunos portadores de deficiência intelectual - Barros, Eliza Philipp Barreiros de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Thinking the school as an institution of equal access for every type of kid, youthful, and adult, to education, It was thought for this assignment to focus in inclusive education in defense of the right of all students to be together, learning and participating without any kind of discrimination. Knowing the large scope of the theme Inclusive Education , subdivided by MEC in four types of disabilities, as follows: auditory, visual, motor and intellectual. It was decided to approach here; intellectual disability, to be a disability that covers a vast number of limitations and that is largely present in the school environment. This work will sought to better understand this deficiency and the work with students carrying it into the classroom

Pensando a escola como instituição de acesso igualitário a todo tipo de criança, jovem e adulto à educação, pensou-se para esse trabalho focar a educação inclusiva em defesa do direito de todos os estudantes de estarem juntos, aprendendo e participando, sem nenhum tipo de discriminação. Sabendo da abrangência do tema Educação Inclusiva, subdividida pelo MEC em quatro tipos de deficiência, sendo elas: auditiva, visual, motora e intelectual, optouse pela deficiência intelectual por ser uma deficiência que abrange diversos tipos de limitações e que também está bastante presente no ambiente escolar. Nesse trabalho será buscado compreender melhor essa deficiência e o trabalho com alunos portadores dela dentro da sala de aula
Keywords: Educação especial; Incapacidade intelectual; Aprendizagem; Educação inclusiva